Hydropower and Dams (H and D) : Strengthening Climate-Informed Project Design - World Bank Water Global Practice (Washington, DC, 2022)
The growing impact of climate change on the design and operations of dams and the inherent complexity of dam projects (often multi-purpose) require the capacity to adopt increasingly strict global standards and to mainstream resilience and low-carbon considerations in water infrastructure in which dams are a critical component. Dams and reservoirs are both helpful for applying water resources management principles to build resilience to climate change and vulnerable to risks related to climate change.